2021
DOI: 10.3390/plants10122758
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Dioxide Nanoparticles Induce Innate Immune Responses and Activate Antioxidant Machinery in Wheat Against Rhizoctonia solani

Abstract: The phytopathogenic basidiomycetous fungus, Rhizoctonia solani, has a wide range of host plants including members of the family Poaceae, causing damping-off and root rot diseases. In this study, we biosynthesized spherical-shaped silicon dioxide nanoparticles (SiO2 NPs; sized between 9.92 and 19.8 nm) using saffron extract and introduced them as a potential alternative therapeutic solution to protect wheat seedlings against R. solani. SiO2 NPs showed strong dose-dependent fungistatic activity on R. solani, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 92 publications
(125 reference statements)
2
17
0
Order By: Relevance
“…Plants suffering from NaCl toxicity often exhibit symptoms associated with oxidative stress and membrane lipid peroxidation, which can result in the accumulation of ROS and MDA (Abdelrhim et al 2021). Salinity stress causes an accumulation of oxidative stress markers such as H 2 O 2 , MDA, and EL (Kaya et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Plants suffering from NaCl toxicity often exhibit symptoms associated with oxidative stress and membrane lipid peroxidation, which can result in the accumulation of ROS and MDA (Abdelrhim et al 2021). Salinity stress causes an accumulation of oxidative stress markers such as H 2 O 2 , MDA, and EL (Kaya et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Three seeds were sown in pots filled with peatmoss: vermiculite potting medium pre-infested with 1% of S. sclerotiorum inoculum grown on sorghum seeds. Inoculum preparation and soil infestation was carried out as per [ 37 , 64 ]. Untreated seeds were sown in S. sclerotiorum -infested soil and virgin soil to serve as a negative control and mock treatment, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Ahamad and Siddiqui [ 72 ] studied effect of SiO 2 -NPs against A. dauci where results revealed that SiO 2 -NPs exhibited promising antifungal activity toward A. dauci and reduced effect of the fungus on carrot. Abdelrhim, et al [ 73 ] reported that the silica nanoparticles significantly reduced mycelial radial growth of Rhizoctonia solani, and also induced innate immune response in wheat. Khan and Siddiqui [ 74 ] used SiO 2 -NPs as seed priming for controlling of R. solani, where results illustrated that SiO 2 -NPs exhibited antifungal activity against R. solani, and this led to enhance growth, chlorophyll and defense enzymes.…”
Section: Resultsmentioning
confidence: 99%